Sistem Keuangan Islam dan Perkembangannya: Kajian Historis Berbasis Prinsip Syariah: Islamic Financial System and Its Development: Historical Study Based on Sharia Principles - Arsyil Arsyil; Niluh Anik Sapitri (HISAB: Jurnal Akuntansi Lembaga Keuangan Syariah, 2026)
This research aims to examine the development of the Islamic financial system through a historical perspective and Sharia principles as its operational foundation. The research method employed is qualitative with a library research approach, utilizing secondary data obtained from relevant scientific literature, academic books, and official reports. Research findings indicate that the Islamic financial system has evolved from simple muamalah practices in the classical period into an institutionalized modern industrial structure in the 20th century. Core principles such as the prohibition of riba, gharar, and maysir serve as an ethical framework ensuring justice, transparency, and risk balance in transactions. The scale of this system continues to increase globally, with total assets reaching approximately USD 4.0 trillion in 2021, driven by the growth of Islamic banking instruments and sukuk. The Islamic financial system demonstrates a high adaptive capability to modern market dynamics through product innovation and the integration of financial technology. The research concludes that the profit-sharing economic model is a sustainable alternative capable of strengthening global financial stability and economic inclusion.